Comparación de las características de movilidad urbana, patrones y parámetros de tránsito, transporte e infraestructura vial de la zona urbana del municipio de Armenia (2007)
Abstract: The complexity and the little planning of our cities throughout history, have brought like consequence the sprouting of an endless number of disarticulated spaces to each other and between the constructions, generating fractures as much at physical level as at cultural and social level. Therefore the necessity to create accessible pedestrians networks, that is born they guarantee the security comfort and well-being for the displacement of all the people. For that reason, it is necessary to understand the accessibility not only like a condition to fulfill in the spaces, constructions and transport I publish of isolated way, but like a articulated, fluid and continuous network between these. As practical case of application of the accessibility indicators, appears an exercise on the network of transport of the city of Armenia (Colombia), in where due to the lack of information values for some variables are assumed you specify, for this case the comparison between the isochronal curves will become of accessibility that this network of transport offers for the city in two scenes, (años 1995 and 2005). Subsequent to this studied the information provided by the isochronal curves, this with the aim to express the advisable conclusions and to establish some improvements that could be implemented in the network.